Features of the Historiography of the Contents of Higher Education Studies in the Western Region of Ukraine the Second Half of XX – Beginning of XXI Century - Tetiana Zavhorodnia; Inna Strazhnikova (Pedagogical Discourse, 2015)
The article discusses the content of higher education in historiographical context, against the background of modern historical and pedagogical researches of the Western region of Ukraine. It is proved that in the Soviet literature, the regional dimension of this problem has not found a profound reflection, 1945-1955 1959-1975, and in General terms only clarified the content and features of the restructuring of academic work and the process of improving educational programs and plans. It analyzes the evolution of the organization and content of the educational process in institutions of higher medical, mathematical, and pedagogical education in Western regions of Ukraine. Among various branches of higher professional education better studied the evolution of medical education at Western in the second half of the XVIII-XX centuries shows the development of a wider range of specialties on which prepare specialists in Ivano-Frankivsk, Lviv, Ternopil, Chernivtsi medical school and the medical faculty of Chernivtsi University. It is proved that the development of the training content of other branches of higher professional education of the Western region of Ukraine has not become the subject of special historical and educational research, but some progress in this direction achieved by the efforts of the representatives of the relevant branches of knowledge. At the same time most thoroughly in the historical-pedagogical studios of the Western lands study of the development of the theory and practice of pedagogical education. Identified promising areas of historical and pedagogical research.